An optimal electric vehicle investment model for consumers using total cost of ownership: A real option approach. (1st November 2019) - Moon, Saedaseul; Lee, Deok-Joo
Highlights: Developing an optimal investment model for EVs considering market uncertainty. Deriving an optimal decision path of EV investment based on fuel price movement. Economic advantages of EVs for consumers with more logged distances. Even without subsidies, EVs are more cost-effective than ICEVs in the Korean market. As fuel price gets more stabilized, the likelihood of adopting EVs should increase. Abstract: Electric vehicles (EVs) are considered as an effective solution in achieving a low-carbon society. One of the major hurdles to EV diffusion is consumer ignorance. That is, consumers generally consider only the initial purchase price, not knowing the total life cycle cost in terms of long-term operational cost savings. The purpose of this study is to develop a consumer-based optimal electric vehicle investment model using total cost of ownership (TCO) which is the actual total cost paid by consumers from acquisition to disposal. Especially, this model includes the recent rapid technological advances in EVs and high volatility of oil prices. To quantify the economic value of the options of consumer's decision, we estimated the TCO of vehicles. Specifically, to provide practical results to consumers, we used the empirical data from the Korean automobile market to evaluate the economic value of TCO. Using the proposed investment model with empirical data, we derived an optimal decision path as a function of time, considering oil price uncertainty and technological advancements, by analyzing a binomial lattice model to identify the optimal timing of adoption. We found that even without subsidies, EVs are more cost-effective than internal combustion engine vehicles (ICEVs) at the current fuel price level, and are still cost-effective even if the current fuel price decreases 20% further in the Korean market. And as the fluctuation of fuel price becomes more stable, consumer preference to EV products should increase.